Characterisation of a high pH cement backfill for the geological disposal of nuclear waste: The Nirex Reference Vault Backfill. (February 2018) - Vasconcelos, Rita G.W.; Beaudoin, Nicolas; Hamilton, Andrea; Hyatt, Neil C.; Provis, John L.; Corkhill, Claire L.
Abstract: In a conceptual UK geological disposal facility for nuclear waste within a high-strength, crystalline geology, a cement-based backfill material, known as Nirex Reference Vault Backfill (NRVB), will be used to provide a chemical barrier to radionuclide release. The NRVB is required to have specific properties to fulfil the operational requirements of the geological disposal facility (GDF); these are dependent on the chemical and physical properties of the cement constituent materials and also on the water content. With the passage of time, the raw materials eventually used to synthesise the backfill may not be the same as those used to formulate it. As such, there is a requirement to understand how NRVB performance may be affected by a change in raw material supply. In this paper, we present a review of the current knowledge of NRVB and results from a detailed characterisation of this material, comparing the differences in performance of the final product when different raw materials are used. Results showed that minor differences in the particle size, surface area and chemical composition of the raw material had an effect on the workability, compressive strength, the rate of hydration and the porosity, which may influence some of the design functions of NRVB. This study outlines the requirement to fully characterise cement backfill raw materials prior to use in a geological disposal facility and supports ongoing assessment of long-term post-closure safety. Graphical abstract: We describe a detailed characterisation of Nirex Reference Vault Backfill (NRVB), a high-pH cement considered for use as a backfill material in a conceptual UK geological disposal facility (GDF) for nuclear waste. We show that the choice of raw materials influences both the mineralogy and microstructure, which are key properties for ensuring the long-term (>100, 000 year) behaviour of this material in a GDF. Image 1